The current landscape of waqf fund for Human Capital Development (HCD) in Malaysia and strategic directions - Mahfuzul Alam Taifur; Asmak Ab Rahman (Penerbit Universiti Kebangsaan Malaysia, 2025)
The contribution of waqf in advancing socio-economic development is both historical and significant, particularly in the context of human capital development (HCD). HCD is essential for producing innovative, skilled, healthy, and educated professionals who can contribute effectively to national growth and competitiveness. As a form of sustainable and ethical financing, waqf plays a pivotal role in supporting HCD initiatives by funding education, healthcare, skills development, and welfare programs. This study aims to explore the current progress of HCD in Malaysia and analyse the role, issues, and challenges faced by waqf in this domain. It further seeks to provide viable recommendations for strengthening the integration of waqf in HCD efforts. The research adopts a qualitative methodology, utilizing data collected from a range of secondary sources including academic books, journal articles, conference papers, and official websites of HCD and waqf institutions. The findings reveal that the potential of waqf funds in supporting HCD is indeed remarkable, with existing initiatives making a positive impact on the socio-economic development of the country. Despite facing various operational, legal, and institutional challenges, the use of waqf in HCD has been commendable. Future research is recommended to explore comparative practices of waqf-based HCD in other jurisdictions to provide deeper insights and benchmarking opportunities for enhancing the Malaysian experience.